Surgical Results of Cervical Spondylotic Amyotrophy - Hamanami, Kazunori; Takeda, Yusuke; Konishi, Akira; Ishii, Hidenori; Imai, Takeshi (Orthopedics & Traumatology, 1996)
We retrospectively evaluated the surgical results of cervical spondylotic amyotrophy in 39 patients (34 men and 5 women) who had been managed between 1973 and 1995. The average age at the time of surgery was 51.2 years (range, 33 to 82 years). Subjects showed muscle atrophy at the shoulder girdle (17 patients), at the forearm and hand (12 patients), and throughout the whole upper extremity (10 patients). Activities of daily living were preoperatively impaired by the muscle weakness. Neurological findings revealed 27 myelopathies and 12 radiculopathies. Anterior interbody fusion (Robinson-Smith) was performed in 35 patients (60 intervertebral discs) and expansive laminoplasty (Hirabayashi) was performed in 4 patients. The average duration of follow-up was 64 months (range, 6 to 164 months). The activities of daily living improved in 31 patients (79%), but in eight patients (21%) they were still impaired. The eight patients preoperatively had all showed myelopathy. In cases of developmental spinal canal stenosis (under 12mm of the sagittal diameter), multiple segmental (over three intervertebral discs) lesions, and generally narrow subarachnoid space, anterior interbody fusion gave poor results. In such cases we recommend the expansive laminoplasty.